The Effect of Business Strategy, Leverage, Profitability and Sales Growth on Tax Avoidance - Lidia Wahyuni; Robby Fahada; Billy Atmaja (Universitas Trisakti, 2017)
This study aims to analyze the effect of business strategy, leverage, profitability and sales growth on tax avoidance. Sample companies involved in tax avoidance were obtained from surveys of manufacturing companies listed on the Indonesia Stock Exchange. The data covers a period of four years from 2014 to 2017. The sample used is secondary data originating from the IDX.com website with the sampling technique that is the purposive sampling method. Data analysis used is a multiple linear regression model. Based on the results of the analysis that has been done, it can be concluded as follows (1) Business strategy has a positive influence on tax avoidance (2) leverage has a positive influence on tax avoidance (3) profitability has no effect on tax avoidance (4) sales growth has an influence positive for tax avoidance